1995
DOI: 10.1021/bi00039a025
|View full text |Cite
|
Sign up to set email alerts
|

Binding and interconversion of tetrahydrofolates at a single site in the bifunctional methylenetetrahydrofolate dehydrogenase/cyclohydrolase

Abstract: The bifunctional dehydrogenase/cyclohydrolase domain of the human NADP-dependent trifunctional methyleneH4folate dehydrogenase/methenylH4folate cyclohydrolase/formylH4folate synthetase (H4folate = tetrahydrofolate) catalyzes two sequential reactions involved in the interconversion of H4folate derivatives. We have established by equilibrium dialysis that a single H4folate-binding site exists per monomer of the dimeric domain and that the presence of nucleotides has two unexpected effects on H4folate substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Thus, the ratio of CH 2 -THF to 10-CHO-THF in the matrix (reactions 3m and 2m in Fig. 1) will be shifted much further toward 10-CHO-THF with a CH 2 -THF dehydrogenase linked to the NAD ϩ /NADH pool versus the NADP ϩ /NADPH pool (6,7). A cyclohydrolase/ dehydrogenase with dual cofactor specificity, such as MTHFD2L, would be able to adapt immediately to changing metabolic conditions, shifting the equilibrium between CH 2 -THF and 10-CHO-THF (and formate) depending on the relative levels of oxidized cofactor (NAD ϩ or NADP ϩ ) in the mitochondrial matrix.…”
Section: Disussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ratio of CH 2 -THF to 10-CHO-THF in the matrix (reactions 3m and 2m in Fig. 1) will be shifted much further toward 10-CHO-THF with a CH 2 -THF dehydrogenase linked to the NAD ϩ /NADH pool versus the NADP ϩ /NADPH pool (6,7). A cyclohydrolase/ dehydrogenase with dual cofactor specificity, such as MTHFD2L, would be able to adapt immediately to changing metabolic conditions, shifting the equilibrium between CH 2 -THF and 10-CHO-THF (and formate) depending on the relative levels of oxidized cofactor (NAD ϩ or NADP ϩ ) in the mitochondrial matrix.…”
Section: Disussionmentioning
confidence: 99%
“…1, reaction 2m). This enzyme, now referred to as MTHFD2, has been extensively characterized with respect to kinetics, substrate specificity, and expression profile (3,(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Kinetic studies suggest that interaction of the poly-g-glutamyl tail of the methylene-tetrahydrofolate molecule with the enzyme provides binding energy and affinity for the substrate, while allowing dynamic motion and kinetic channeling of the reactive methenylpterin ring system between dehydrogenase and cyclohydrolase active sites~Cohen & MacKenzie, 1978;Wasserman et al, 1983;Green et al, 1988;Hum & MacKenzie, 1991;Pelletier & MacKenzie, 1995!. Inspection of the surface of the E. coli dph0cyc revealed that there are two significant regions of positive-charged residues, one at each end of the cleft between the two a0b domains of deh0cyc.…”
Section: Putative Methylene-tetrahydrofolate Binding Sitementioning
confidence: 99%
“…The methenyl-THF product of the dehydrogenase reaction displays significant kinetic "channeling" to the cyclohydrolase active site, where it is converted to formyl- THF~Cohen & MacKenzie, 1978;Wasserman et al, 1983;Hum & MacKenzie, 1991;Pelletier & MacKenzie, 1995!. Several chemical studies indicate that the deh and cyc active sites are in close proximity and might overlap~Schirch, 1978; Drummond et al, 1983;Appling & Rabinowitz, 1985!.…”
mentioning
confidence: 99%
“…The NADPH/NADP + ratio in turn may play an important role in regulating the cytosolic flux of 1C units through the MTHFD1 dehydrogenase reaction. The relatively high NADPH/NADP + ratio in the cytosol may favor reduction of 1C units from 10-formyl-THF into methylene-THF, whereas low NADH levels in the mitochondria favor the opposite (Pelletier and MacKenzie, 1995).…”
Section: Introductionmentioning
confidence: 99%